Upper limb muscle activation in elite ski-mountaineers during simulated sprints on snow - Todesco, B.; Lorenzo, B.; Verdel, N.; Majeric, M.; Holmberg, H.-C.; Supej, M.; Barbara, P. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Ski mountaineering (SkiMo) is gaining prominence as it becomes part of the Milano-Cortina 2026 Winter Olympics, yet scientific literature on the discipline remains limited. Sprint competitions, as described by Fornasiero et al. [1], emphasize the importance of optimal performance during transitions and uphill sections, with training focusing on supramaximal efforts lasting 1.5-2.5 minutes. This study investigates upper body muscular activity during polepushing in flat and uphill sections, analyzing activation patterns and cycle time to better understand the biomechanical demands of sprint ski-mountaineering in elite athletes.